KEMUDAHAN PENGGUNAAN SISTEM PERSEPSIAN SEBAGAI FAKTOR DETERMINAN (STUDI PADA RSUD Dr. SAIFUL ANWAR MALANG) - Sanyana, Gita Mian Dame (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to examine the determinant factors of individual perceived ease of use based on Technology Acceptance Model (TAM). This research is conducted at RSUD Dr. Saiful Anwar Malang. The primary data are obtained through questionnaires which are distributed towards 186 employees selected purposively as the research samples. The data are analyzed by hypothesis testing with SmartPLS 2.0. The result of the analysis show that computer playfulness and perceived enjoyment are affect perceived ease of use. Individuals who are pleased and comfortable tend to feel easy at applying the computer system. On the other hand, self-efficacy, facilitating conditions, and computer anxiety are proven to have no influence toward perceived ease of use.Keywords : Technology Acceptance Model, Perceived Ease of Use, Perceived Enjoyment, Computer Playfulness.